Culture, technology and sustainable development: a rational utilization of the nigerian built environment (2007)
The paper sought to discuss the meaning and essence of technology and culture in the management and sustainability of the built environment. It enumerates the urban development process, concept of sustainability as it affects the quality of the built environment. It examines in details, the principles and values of culture as indicators for the sustainability of the environment. The paper concludes by recommending for the enactment and enforcement of relevant policies with adequate education of the entire people and the involvement of all the stakeholders in the management of the environmental programmes taking absolute cognizance of the people’s culture